Microbial Contamination Of Dried Chillies, Chilli Pastes, And Chilli Powder Sold At Retail Market In Penang - Samsudin, Nurul Afifah (Pusat Pengajian Teknologi Industri, 2021)
Chillies have been used as one of the main ingredients in various local dishes in Malaysia to give visual appeals, colour, taste and hot sensation. However, chilli products are prone to fungal contamination especially Aspergillus spp., Fusarium spp. and Penicillium spp. during preharvest, harvest, and postharvest if the conditions are favourable for its growth and the hygiene of chilli products still uncertain. This study was aimed to determine the microbial contamination of dried chillies, chilli pastes, and chilli powder sold at retail market in Penang. Fifteen packaged chilli samples were collected and analysed for Total Plate Count (TPC), coliform count, total fungal count and fungal identification.